Consociationalism and Identity in Ethnically Divided Societies: Northern Ireland and Malaysia. (December 2016) - Jarrett, Henry
Abstract: This article tests the hypothesis that ethnic identities in divided societies lose their significance after the implementation of consociational power‐sharing arrangements. It analyses and compares the cases of Northern Ireland and Malaysia, as both have a substantially different experience of liberal consociationalism. In Northern Ireland, power sharing is strictly enforced through the Good Friday (Belfast) Agreement of 1998, whilst in Malaysia it is exercised more informally within the Barisan Nasional coalition, which has governed the state since independence in 1957. Malaysia, therefore, has a considerably longer history of consociationalism than Northern Ireland. It is thought that if a mitigation of the salience of ethnic identities is taking place, ethnic political parties would become less prevalent. This article argues that these parties remain highly significant and, therefore, a shared identity is not being realized in either case. This conclusion does not, however, demonstrate a shortcoming of consociational theory but instead shows that managing conflict in divided societies is not the same as removing it altogether.